CONTRIBUTION OF PROFESSOR A.S. BASHKIROV (1885-1963) IN THE STUDY OF MONUMENTS OF MEDIEVAL ART OF DAGESTAN - Mammaev, Misrihan Mamaevic (History, Archeology and Ethnography of the Caucasus, 2023)
: The article highlights the scientific activities of prof. Alexei Stepanovich Bashkirov in the 20s - early 30s of the XX century. on the study of monuments of medieval art of Dagestan. It examines his scientific works, noting both valuable observations regarding the decorative qualities of the works of art he studied, as well as individual not entirely correct judgments about the plots and images of stone and wood carving monuments, and not entirely convincing analogies he cites. It is noted that A.S. Bashkirov was the first researcher who began studying many monuments of Dagestan art from the art criticism positions. He was the first to describe a stone tombstone in the form of a sarcophagus of the XIII century from the village. Kalakoreish, decorated with pictorial subjects and ornaments in combination with a late Kufic Arabic inscription. He also described the highly artistic decoration of two pairs of wooden doors of the cathedral mosque c. Kalakoreish. He was the first to study the petrographic monuments of Dagestan. He also studied stone reliefs - details of architectural decoration from the village. Kubachi. For the first time, he introduced many monuments of the stone-cutting art of mountainous Dagestan into scientific circulation. For the main research work, A.S. Bashkirov "Art of Dagestan. Carved stones ”(M., 1931) Camilla Vasilievna Trever (1892-1974) wrote a sharply negative review. Later, the review was used by the investigators as evidence against A.S. Bashkirov when he was arrested (January 8, 1935), accusing him of "counter-revolutionary activities". The article notes that in 1935 A.S. Bashkirov and together with him Moscow scientists, professors I.N. Borozdin and A.A. Zakharov were repressed. They were exiled for 3 years to Kazakhstan "for counter-revolutionary activities." After returning from exile, A.S. Bashkirov and I.N. Borozdin worked as teachers in higher educational institutions. A.A. Zakharov was shot in 1937. The article emphasizes that A.S. Bashkirov, through his work, made a certain contribution to the history of the art of Dagestan, that he was the initiator of Dagestan art history.
Keywords: Professor A.S. Bashkirov; researcher of Dagestan art; Middle Ages; stone and wood carving; repression